2010
DOI: 10.1007/s12155-009-9073-7
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Communities in the Rhizosphere of Biofuel Crops Grown on Marginal Lands as Evaluated by 16S rRNA Gene Pyrosequences

Abstract: Microbes are key components of the soil environment and are important contributors to the sustainability of agricultural systems, which is especially significant for biofuel crops growing on marginal lands. We studied bacterial communities in the rhizosphere of five biofuel crops cultivated in four locations in Michigan to determine which factors were correlated to changes in the structure of those communities. Three of these sites were marginal lands in that two were not suitable for conventional agriculture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…The microbial compositions of Chinese fir plantations of different ages were different. The bacterial dominance of Acidobacteria, Proteobacteria, Actinobacteria, Chloroflexi, and Firmicutes and the fungal dominance of Ascomycota, Basidiomycota and Zygomycota in the present study have been observed in various soils types [45][46][47][48][49], indicating that these microbial phyla play important roles in soil ecosystems. Changes in microbial community composition indicate changes in soil ecological environment and function [50,51].…”
Section: Shift In Soil Enzyme Activities and Composition And Diversity Of Microbial Communitiessupporting
confidence: 53%
“…The microbial compositions of Chinese fir plantations of different ages were different. The bacterial dominance of Acidobacteria, Proteobacteria, Actinobacteria, Chloroflexi, and Firmicutes and the fungal dominance of Ascomycota, Basidiomycota and Zygomycota in the present study have been observed in various soils types [45][46][47][48][49], indicating that these microbial phyla play important roles in soil ecosystems. Changes in microbial community composition indicate changes in soil ecological environment and function [50,51].…”
Section: Shift In Soil Enzyme Activities and Composition And Diversity Of Microbial Communitiessupporting
confidence: 53%
“…In contrasting soils, such as deserts and forests, significantly fewer FP-CAZy core sequences could be identified, suggesting that the soil environment, which can be geographically specific, is important for defining a soil core and its functional potential. This result has been reported previously where soil type was the critical driver of microbial community compositional differences [53,54]. For metagenomic studies, this observation has implications for the genomic or functional level that should be compared between studies.…”
Section: Discussionsupporting
confidence: 82%
“…DNA extraction and SSU rRNA gene amplification methods were described previously (29). The SSU rRNA gene amplicons from the first sample were sequenced by the Joint Genome Institute (JGI) in their standard work flow, which used 454 GS FLX and Titanium platforms and a primer set (926F, AAACTYAAAKGAATTGACGG; 1392R, ACGGGCGG TGTGTRC) that targeted the V6-V8 variable region of bacteria, archaea, and eukaryotes.…”
Section: Methodsmentioning
confidence: 99%